2023
DOI: 10.3390/polym15193865
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Anti-washout Property of Acrylate Grouting Material by Bentonite: Its Characterization, Improving Mechanism, and Practical Application

Zuochun Li,
Feng Huang,
Yuyou Yang
et al.

Abstract: Acrylate is a popular polymer grouting material that has been widely used to control groundwater seepage. However, the vulnerability of acrylate slurry to dynamic water washout restricts its application in groundwater environments characterized by high flow velocity and water pressures. In this paper, lithium bentonite (Li-B) was used to modify the traditional magnesium acrylate (AC) grouting material. The influence of Li-B to AC ratios on the modified materials’ washout resistance was explored, and the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Nautts [17], Saleh et al [18], and Hao et al [19] reported that polyurethane materials have a high degree of curing and strong erosion resistance. Sun et al [20], Zheng et al [21], and Li et al [22] studied the basic properties of a cementitious capillary crystalline waterproofing (CCCW) material and explored its feasibility for treating tunnel leakage diseases. Ebigbo et al [23] and Van Wjngaarden et al [24] used a microbial-induced calcium carbonate precipitation to solidify sandy soil and combined experimental and numerical simulations to study the bacterial behavior, distribution of calcium carbonate, and changes in permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Nautts [17], Saleh et al [18], and Hao et al [19] reported that polyurethane materials have a high degree of curing and strong erosion resistance. Sun et al [20], Zheng et al [21], and Li et al [22] studied the basic properties of a cementitious capillary crystalline waterproofing (CCCW) material and explored its feasibility for treating tunnel leakage diseases. Ebigbo et al [23] and Van Wjngaarden et al [24] used a microbial-induced calcium carbonate precipitation to solidify sandy soil and combined experimental and numerical simulations to study the bacterial behavior, distribution of calcium carbonate, and changes in permeability.…”
Section: Introductionmentioning
confidence: 99%